Design and Development of a Web-Based Employee Safety Training Management Information System Using the Laravel Framework at "PT Meares Soputan Mining - Nathanael Eduard Ronny Taiwiland; Ilham Majidi; Arthur Hizkia Manoppo; Vita Ponggawa; Josephin Sundah (Journal of Social Research, 2026)
Occupational health and safety (OHS) is a critical concern in the mining industry due to high-risk work environments that expose employees to accidents and health hazards. At PT Meares Soputan Mining, conventional safety training management using spreadsheets and physical documents has resulted in operational inefficiencies, including delays in tracking compliance, risk of data loss, and cumbersome reporting processes. This study aims to design and develop a web-based Employee Safety Training Management Information System using the Laravel framework to automate training administration, monitor real-time compliance, and generate comprehensive reports for management decision-making. The research employed a mixed-methods approach, including direct observation of safety training administration, in-depth interviews with key informants from the HSE department, and document analysis of existing SOPs and training records. The system architecture adopts a three-tier design with MySQL database integration, Eloquent ORM, Blade templating, and automated notification features. Black-box testing and User Acceptance Testing (UAT) were conducted to assess functionality, usability, and performance. Results indicate that the system successfully reduced report preparation time from 8 hours to 25 minutes, improved training compliance tracking, and received high user satisfaction scores (mean 4.31 out of 5). The discussion highlights Laravel's effectiveness in managing complex data relationships and supporting mining-specific safety requirements. In conclusion, the system enhances operational efficiency, regulatory compliance, and workforce safety, offering a scalable solution for mining safety management.